2020
DOI: 10.3390/ijms21175958
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Antimicrobial Activity of Endophytic Fungi Isolated from Chloranthus japonicus Sieb in Qinling Mountains, China

Abstract: The plant Chloranthus japonicus Sieb is known for its anticancer properties and mainly distributed in China, Japan, and Korea. In this study, we firstly investigated the diversity and antimicrobial activity of the culturable endophytic fungi from C. japonicus. A total of 332 fungal colonies were successfully isolated from 555 tissue segments of the medicinal plant C. japonicus collected from Qinling Mountains, China. One hundred and thirty representative morphotype strains were identified according to ITS rDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
2
15
1
Order By: Relevance
“…In our previous study, it was found that there was some similarity between the endophytic fungi composition of C. japonicus Sieb (dominant genera: Colletotrichum, Aspergillus, and Diaporthe ) and that of T. chinensis Baker (dominant genera: Collectotrichum, Fusarium, Aspergillus ) from Yingpan town (Qinling Mountains region), Shaanxi province of China. However, the results obtained in this study (dominant genera: Plectosphaerella, Paraphoma, and Fusarium ) showed significant difference from those of the aforementioned studies ( An et al, 2020a ; An et al, 2020b ). Also, rare genera such as Lecanicillium , Sarocladium , Thelonectria , Valutella , Exserohilum , Flavodon , and Rigidoporus obtained in this study were quite different from those in our previous studies, including Biscogniauxia , Leptostroma , Stachybotrys , Didymella , Peniophora , Peniophora , Rhodotorula , Setophaeosphaeria , Clitopilus , Muyocopron , Thanatephorus , and Ceriporia .…”
Section: Discussioncontrasting
confidence: 97%
“…In our previous study, it was found that there was some similarity between the endophytic fungi composition of C. japonicus Sieb (dominant genera: Colletotrichum, Aspergillus, and Diaporthe ) and that of T. chinensis Baker (dominant genera: Collectotrichum, Fusarium, Aspergillus ) from Yingpan town (Qinling Mountains region), Shaanxi province of China. However, the results obtained in this study (dominant genera: Plectosphaerella, Paraphoma, and Fusarium ) showed significant difference from those of the aforementioned studies ( An et al, 2020a ; An et al, 2020b ). Also, rare genera such as Lecanicillium , Sarocladium , Thelonectria , Valutella , Exserohilum , Flavodon , and Rigidoporus obtained in this study were quite different from those in our previous studies, including Biscogniauxia , Leptostroma , Stachybotrys , Didymella , Peniophora , Peniophora , Rhodotorula , Setophaeosphaeria , Clitopilus , Muyocopron , Thanatephorus , and Ceriporia .…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast to the dominance of Colletotrichum spp. in these medicinal plants (Tan et al, 2018;An et al, 2020), Penicillium followed by Aspergillus were the most dominating fungal taxa in the current study. In another study on fungal endophytes isolated from Rhodiola spp.…”
Section: Microbial Communities In a Euchromamentioning
confidence: 56%
“…For example, Tan et al (2018) reported 93% occurrence of Ascomycota in Dysosma versipellis. An et al (2020) reported endophytic fungal diversity of Chloranthus japonicus, where 97.89% of endophytes belonged to the Ascomycota phylum. In contrast to the dominance of Colletotrichum spp.…”
Section: Microbial Communities In a Euchromamentioning
confidence: 99%
“…Du et al (2020) reported colony growth inhibition of Colletotrichum siamense only by 3.6-26.3% under the influence of endophytic fungi from Securinega suffruticosa roots, stems and leaves. The endophytic fungi isolated from the tissues of Chloranthus japonicus exhibited good antagonistic capacities (the percent inhibition of mycelial growth ranged 47.72-88.18%) against different pathogens (An et al, 2020). Thus, antagonistic ability of the endophytic isolates derived from the peel and pulp of Ch.…”
Section: Discussionmentioning
confidence: 96%